Study of Dental Cast and Cephalometric in Unoperated Adult UCLP Patients - Benny S. Latief (Faculty of Dentistry, Universitas Indonesia, 2013)
Background: Early operated patients with orofacial clefts often develop a retrusive maxilla. It is not clear whether this growth disturbance is attributed to the congenital malformation itself or to the cleft surgery or both. Objective: to evaluate transversal and anterio-posterior maxillary development in unoperated adult patients with unilateral cleft lip and palate (UCLP). Methods: 68 dental casts of unoperated adult UCLP patients were compared to 24 adult controls. The casts were analyzed three dimensionally using an industrial coordinate measuring machine (=CMM) (Zeiss Numerex; Carl Zeiss Stutgart, Germany). 12 cephalograms of unoperated UCLP patients and 24 controls were available and measured for the following variables: Maxillary length, SNA, SNB, Gonial angle and SN-FH angle. The data obtained was analysed by paired t-test, level of significance was set at p<0,05. Results: measured on dental casts, the transversal distance at the level of the second molars was significantly smaller compared to the control group. Cephalometrically there were no significant difference for the 5 cephalometic measurements. Conclusion: the presence of a cleft influences the development of the maxilla: the more extensive the cleft, the more extensive the effect on the dental arch, but the compression of the maxillary arch is limited to the anterior regio. Measured cephalometrically the cleft has no influence on the development of the maxilla. However, the sample size for the cephalometric study was small. DOI: 10.14693/jdi.v16i3.105